Increasing Interest in Learning Indonesian Using the Smart Snakes and Ladders Learning Media in Class 1A Students - Adieza Putri, Nursyifa Fadilla; Rakhman, Patra Aghtiar; Rokmanah, Siti (JUPE : Jurnal Pendidikan Mandala, 2023)
Classroom learning becomes a space for teacher actualization in applying creative learning media. The use of creative learning media is important for teachers in the teaching and learning process with students. Using varied strategies will reduce students' levels of boredom and will increase students' interest in learning. This research method is qualitative research in which researchers directly carry out observations and interviews in the field located in class 1A of SDN Sumampir. The research subjects themselves were students in class 1A. It is hoped that it will be able to arouse interest and stimulate learning activities in students, help the effectiveness of the learning process, attract and direct students' attention to concentrate on the content of the lesson, facilitate the achievement of goals to understand and remember the information provided, make learning more interesting, bring freshness and new variations. for students' learning experiences, especially in Indonesian language subjects. From the above, researchers have learning media that can be a solution and can be developed, namely "Smart Snakes and Ladders". In this media, researchers want class 1A students at SDN Sumampir to be more familiar with letters so they can read fluently. The media that the researchers developed aims to enable students to continue playing without realizing that they are actually learning. In terms of the average test scores before implementing the smart snakes and ladders learning media, the average score for daily tests chapters 1 – 4 was 68.78. After implementing using smart snakes and ladders, daily tests were carried out in chapters 5 – 8, the average score was 88.83. It can be seen that the value has increased drastically. This indicates that class 1A students at SDN Sumampir prefer learning Indonesian using creative learning media such as smart snakes and ladders. Apart from that, smart snakes and ladders are said to have succeeded in increasing students' interest in learning Indonesian.